BRAIN STORMING AND DEMONSTRATION CHANGE MOTHER'S BEHAVIOR TOWARD BREASTMILK COMPANION FOOD - Mira Triharini; Retnayu Pradanie; Halimatus Zahrah (Universitas Airlangga, 2017)
Introduction: Infant on 0-6 months must be gotten exclusive breast milk from their mother for growth and development status. It was mean that no other food for infant. The objective of this study was to expalain the the effect of brain storming and demonstration about exclusive breastfeding on mother's behaviour ( knowledge, attitude and practice) in giving breastmilk companion food for infant (0-6 month) at Bung Baruh's Village,  Pamekasan. Method: This study used one group pre-test post-test design. Population were mothers in those area, and sample were 32 respondents who met the inclusion criteria. The independent variable were health education with brain storming and demonstration methods. The dependent variable were mother's behaviour (knowledge, attitude and practice) in giving food beside mother's milk for infant. The data were analyzed by using Wilcoxon Signed Rank Test with significance level α≤ 0.05. Result: The result showed that brain storming and demonstration had effect on mother's behaviour  (knowledge p=0.000; attitude p= 0.033; and practice p=0.000) in giving breastmilk companion food for infant (0-6 month). Analysis:  It can be concluded that brain storming and demonstration has an effect on mother's behaviour ( knowledge, attitude and practice) in giving breastmilk companion food for infant (0-6 month). Discussion: Brainstorming can be alternative choice for changing mother's health behaviour.